Halal Dim Sum as A Chinese Muslim Culinary Heaven in The Heart of Surabaya City - Mularsari, Ardi; Jehan Achmad, Vickrham Shah; Martha Ananda, Tiara (Jurnal Toursci, 2024)
This study examines the development of halal dim sum restaurants in Surabaya, Indonesia, as a manifestation of culinary adaptation and cultural interaction in the context of a multicultural urban society. Surabaya, the second-largest city in Indonesia, has long been known for its culinary diversity. However, the emergence of halal dim sum restaurants represents a new trend that reflects changes in demographics, consumer preferences, and socio-cultural dynamics. Through a qualitative approach, this study explores the process of adapting traditional Cantonese dim sum into a halal version that meets Islamic Sharia standards without sacrificing the authenticity of the taste. This study analyzes various aspects, including ingredient substitution, modification of cooking techniques, menu innovation, and marketing strategies implemented by halal dim sum restaurants in Surabaya. Key findings suggest that the success of halal dim sum lies not only in culinary innovation but also in its ability to bridge the Chinese and Muslim communities. This phenomenon creates a new space for social interaction and cultural exchange while also encouraging the development of the creative economy in the culinary sector. Furthermore, this study reveals that halal dim sum serves as a catalyst in shaping Surabaya's new, more inclusive culinary identity. The implications of this study provide valuable insights into how culinary adaptation can be instrumental in promoting social cohesion and tolerance in diverse urban communities.